Clinicopathologic analysis of oral dermoid and epidermoid cysts: a Brazilian multicenter study - Cunha, John Lennon Silva; de Oliveira Andrade, Allany; Cavalcante, Israel Leal; da Silva Barros, Caio César; de Sousa Neto, Sebastião Silvério; de Barros, Joyce Magalhães; da Silva Leite, Larissa Sandy [UNESP]; Félix, Fernanda Aragão; Turatti, Eveline; Carvalho, Francisco Samuel Rodrigues; de Sousa, Sílvia Ferreira; de Mendonça, Elismauro Francisco; et al. (FapUNIFESP (SciELO), 2023)
Dermoid cysts (DCs) and epidermoid cysts (ECs) are uncommon developmental cysts affecting the oral cavity. This study aims to evaluate patients with oral DCs and ECs and their demographic and clinicopathologic features. A retrospective descriptive crosssectional study was performed. A total of 105,077 biopsy records of oral and maxillofacial lesions from seven Brazilian oral pathology centers were analyzed. All cases diagnosed as oral DCs and ECs were reviewed, and clinical, demographic, and histopathological data were collected. The series comprised 32 DCs (31.4%) and 70 ECs (68.6%). Most of the DCs occurred on the floor of the mouth (n = 14; 45.2%) of women (n = 17; 53.1%) with a mean age of 34.6 ± 21.6 years. All DCs were lined partially or entirely by stratified squamous epithelium (100%). Chronic inflammatory cells, melanin pigmentation, multinucleated giant cell reaction, and cholesterol clefts were observed in the fibrous capsule. Most of the ECs affected the labial mucosa (n = 20; 31.7%) of men (n = 39; 56.5%) with a mean age of 48.0±19.8 years. Microscopically, most ECs (n = 68; 97.1%) were lined entirely by stratified squamous epithelium. Two cysts (2.9%) showed areas of respiratory metaplasia. Chronic inflammatory cells, melanin pigmentation, multinucleated giant cell reaction, and cholesterol clefts were also observed in the fibrous capsule. Conservative surgical excision was the treatment of choice in all cases. Oral DCs and ECs are uncommon and often clinically misdiagnosed lesions. Clinicians should consider DCs and ECs in the differential diagnosis of soft tissue lesions in the oral cavity, mainly located on the floor of the mouth and labial mucosa.
Keywords: Dermoid Cyst; Epidermal Cyst